Embedding the Scientists: Civic Issues as Context for Teaching and Learning - Heather Lettner-Rust; Alix Dowling Kink; Edward Kinman; JoEllen Pederson; Phillip Poplin (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
We teach science as a path to meaningful civic engagement in a participatory democracy and as a path that should be open to all; our concern lies in how the next generation of young citizens1 address challenging civic issues both by applying science to other contexts—public and civic—as well as communicating science to others—peers and the public. To that end, our article seeks to explain an interdisciplinary capstone course for our general education program that we developed to promote and support science learning and science communication by teaching in the context of important civic issues.